Pre- and Post-Procedural Considerations and Thread Types for Thread Lifting - Gi-Woong Hong; Jovian Wan; Song-Eun Yoon; Sky Wong; Kyu-Ho Yi (Life)
Facial thread lifting has emerged as a minimally invasive alternative to traditional face-lifting procedures, with particular emphasis on U-shaped and I-shaped barbed threads. This review analyzes the anatomical considerations, procedural techniques, and clinical outcomes of different thread types for facial rejuvenation. The study examines the mechanical principles and lifting mechanisms of U-shaped “suspension type” threads versus I-shaped threads, highlighting their distinct characteristics and applications. The results indicate that U-shaped threads provide strong lifting effects, with success rates reported at 85–90% in achieving visible tissue elevation when anchored in the temporal area. However, these threads carry higher risks of complications, including bleeding (15–20%), dimpling (12–18%), and tissue damage at exit points (5–10%). In contrast, I-shaped threads demonstrate advantages in minimizing tissue trauma and patient discomfort, with complication rates below 5%, though they may provide less dramatic lifting effects. The study concludes that optimal outcomes are achieved through careful patient selection and customized combination approaches rather than reliance on a single thread type. Future directions point toward the development of hybrid techniques that combine the strengths of both thread types to maximize efficacy while minimizing complications.